Practice of banking 2 (Ilorin, Nigeria : Oak Professional Publishing in Association with BPP Publishing Ltd., 1993)
This text is designed as a comprehensive course covering the syllabus of the Practice of Banking 2.
osc 21/09/2017, ijb 11/03/2019
Loans
Keywords: Banking; Banking practice; Bank lending; Marketing - financial services